Gastrointestinal Bleeding as a Clinical Manifestation of Strongyloides stercoralis Hyperinfection in a Patient with HIV: A Case Report - Badaró, Pedro Felipe Miranda; Machado, Cláudia de Abreu Cardoso; de Freitas, Luiz Antônio Rodrigues; Branco, Renata Dias Araujo; da Silva, Bruno César (Journal of Gastrointestinal Infections, 2024)
Strongyloidiasis, caused by the nematode Strongyloides stercoralis, is an often neglected parasitic disease, with deeper prevalence in tropical and subtropical regions. This parasitic infection can range from asymptomatic to symptomatic, with nonspecific manifestations, including gastrointestinal symptoms. Herein, we reported the case of an human immunodeficiency virus (HIV)-positive patient, under effective antiretroviral treatment with a normal CD4 count, who was hospitalized due to gastrointestinal bleeding. The diagnosis of strongyloidiasis hyperinfection was confirmed following endoscopic biopsies of both the gastric and duodenal mucosa. Subsequently, a treatment regimen of ivermectin at a dosage of 200 mcg/kg/day for a duration of 14 days was initiated, leading to notable amelioration in the patient's clinical presentation. In considering the differential diagnosis of gastrointestinal bleeding, it is crucial to explore various possibilities, including peptic ulcers, portal hypertension, and cancer. Among immunocompromised individuals like those with HIV, chronic infection can compromise the Th2 immune response, which is pivotal in combating helminthic infections. This underscores the importance of remembering intestinal parasitosis, particularly strongyloidiasis, in such cases. Even in patients with preserved CD4 counts, careful evaluation for opportunistic infections in HIV-positive individuals is paramount. Early initiation of treatment is essential to mitigate the risk of serious complications.
Keywords: gastrointestinal bleeding; HIV; strongyloidiasis